Advanced Molecular-Genetic Methods and Prospects for Their Application for the Indication and Identification of Yersinia pestis Strains - K. A. Nikiforov (Проблемы особо опасных инфекций)
The review provides an analysis of the literature data on the use of various modern molecular-genetic methods for the indication and identification of Yersinia pestis strains with different properties and degree of virulence, which is caused by the diverse natural conditions in which they circulate. The methods are also considered from the perspective of their promising application at three levels (territorial, regional and federal) of the system for laboratory diagnosis of infectious diseases at the premises of Rospotrebnadzor organizations to solve the problem of maintaining the sanitary and epidemiological well-being of the country’s population. The main groups of methods considered are as follows: based on the analysis of the lengths of restriction fragments (ribo- and IS-typing, pulse gel electrophoresis); based on the analysis of specific fragments (DFR typing, VNTR typing); based on sequencing (MLST, CRISPR analysis, SNP analysis); PCR methods (including IPCR, SPA); isothermal amplification methods (LAMP, HDA, RPA, SEA, PCA, SHERLOCK); DNA-microarray; methods using aptamer technology; bio- and nano-sensors; DNA origami; methods based on neural networks. We can conclude that the rapid development of molecular diagnostics and genetics is aimed at increasing efficiency, multi-factorial approaches and simplifying the application of techniques with no need for expensive equipment and highly qualified personnel for analysis. At all levels of the system for laboratory diagnosis of infectious diseases at the Rospotrebnadzor organizations, it is possible to use methods based on PCR, isothermal amplification, SHERLOCK, biosensors, and small-sized sequencing devices. At the territorial level, at plague control stations, the use of immuno-PCR and SPA for the indication of Y. pestis is viable. At the regional level, introduction of the technologies based on the use of aptamers and DNA chips looks promising. For the federal level, the use of DNA origami methods and new technologies of whole genome sequencing is a prospect within the framework of advanced identification, molecular typing and sequencing of the genomes of plague agent strains.